Inflammation as a contributing factor among postmenopausal Saudi women with osteoporosis - Al-Daghri, Nasser M. (Medicine (Baltimore), 2017)
Postmenopausal osteoporosis is an important metabolic bone disease characterized by rapid bone loss occurring in the postmenopausal period. Recently, the most prevalent form of clinically significant osteopenia and osteoporosis involves various inflammatory conditions. The aim of the study is to evaluate the association between proinflammatory markers (interleukin [IL]-1β, IL-6, TNF-α) with bone turnover markers (BTMs) in postmenopausal Saudi women with and without osteoporosis. A total of 200 postmenopausal Saudi women ≥50 years old, 100 with osteoporosis and 100 without osteoporosis (control) were recruited under the supervision of qualified physicians in King Salman Hospital and King Fahd Medical City, Riyadh, Saudi Arabia. Serum tumor necrosis factor alpha (TNF-α), IL-1, IL-4, IL-6, and parathyroid hormone (PTH) were determined using Luminex xMAP technology. N-telopeptides of collagen type I (NTx) was assessed using ELISA, 25(OH) vitamin D and osteocalcin were determined using electrochemiluminescence, serum calcium and inorganic phosphate (Pi) were measured by a chemical analyzer. Serum IL-1β, IL-6, NTx, and PTH levels in women with osteoporosis were significantly higher than controls. Although IL-4 and osteocalcin were significantly lower than controls. IL-1β and TNF-α were positively associated with NTx in osteoporosis women. TNF-α, IL-6, and TNF-α were positively correlated with IL-lβ in both groups. A significant negative correlation between osteocalcin and IL-1β in healthy women and women with osteoporosis were observed. Findings of the present study implicate a role for cytokine pattern-mediated inflammation in patients with osteoporosis.